Pengaruh Pendidikan Kesehatan Terhadap Tingkat Pengetahuan da Sikap Keluarga Dalam Memberikan Perawatan pada Penderita Asma - Arta Winangsit; Sahuri Teguh (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2015)
Background: Asthmatics in Indonesia from year to year so increase. Most people do not control because it considers asthma is a common disease and is not harmful, but many people died bacause asthma. Objective: This study to know influence of Health Education to changes in the level of knowledge and attitudes of families in delivering care in Patients with Asthma. Method: Type of this research used quasi experimental with pretest-posttest control group design. The sample are family with asthma who live in the Sruni village with a population of 44 peoples, divided 22 for experimental group and 22 for control group. Mechanical sampling with proportional random sampling. Result: Results of the research show there is influence of health education on knowledge and attitude of the family in providing care asthmatics in the Sruni, Musuk, Boyolali village.